2020
DOI: 10.3390/s20051426
|View full text |Cite
|
Sign up to set email alerts
|

Local Wireless Sensor Networks Positioning Reliability Under Sensor Failure

Abstract: Local Positioning Systems are collecting high research interest over the last few years. Its accurate application in high-demanded difficult scenarios has revealed its stability and robustness for autonomous navigation. In this paper, we develop a new sensor deployment methodology to guarantee the system availability in case of a sensor failure of a five-node Time Difference of Arrival (TDOA) localization method. We solve the ambiguity of two possible solutions in the four-sensor TDOA problem in each combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…This study requires the characterization of the system noise errors [22], the consideration of the clock errors [26], the detection of LOS/NLOS paths in the positioning signal links of each architecture [41], the guarantee of the availability of the TBS under possible sensor failures [47] and a methodology that enables a costeffective node deployment for each architecture [25].…”
Section: Problem Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study requires the characterization of the system noise errors [22], the consideration of the clock errors [26], the detection of LOS/NLOS paths in the positioning signal links of each architecture [41], the guarantee of the availability of the TBS under possible sensor failures [47] and a methodology that enables a costeffective node deployment for each architecture [25].…”
Section: Problem Definitionmentioning
confidence: 99%
“…The definition of the necessary nodes for covering the target area (i.e. coverage problem [52]), the consideration of possible sensor failures in the deployment [47], the reduction of the energy consumption [53] or the minimization of the clock [26] and noise [41] uncertainties are some of the most important issues in WSN that require an optimized sensor location for achieving acceptable results.…”
Section: Node Location Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows us to avoid synchronism among the system receivers, consequently reducing the architecture clock errors [ 20 ] but increasing the signal paths and noise errors [ 21 ], since they rely on a receive-and-retransmit strategy of the positioning signals in the Target Sensor (TS), producing longer path signals. In addition, a possible CS malfunction may produce temporal system unavailability [ 22 ] due to the particular architecture dependence on the CS.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous research, we have applied GA to the NLP in LPS [ 7 , 20 , 21 , 22 , 30 ]. In these papers, we have observed that the dimensions of the space of solutions which increases with the number of sensors, the resolution of the pre-defined possible space locations for them and the complexity of the fitness function evaluation, significantly affect the stable performance of the GA.…”
Section: Introductionmentioning
confidence: 99%